Nachtschattengewächse. : Leitmotive - Räume - Gäste - Diedrichsen, Diedrich; Avgikos, Jan; Loers, Veit (Kassel : Museum Fridericianum, 1993)
Herold, Georg ; Kippenberger, Martin ; Lawler, Louise ; Mucha, Reinhard ; Schütte, Thomas ; Calle, Sophie ; Cattelan, Maurizio ; Clark, Larry ; Drescher, Jürgen ; Hirst, Damien ; McCaslin, Matthew ; Miller, John ; Parrino, Steven ; Stingel, Rudolf ; Zobernig, Heimo ; Arió, Mario ; di Benedetto, Steve ; Fonzalez-Torres, Félix ; Kozaris, Dimitris ; Roth, dieter ; Thek, Paul ; Weigand, Hans
Nachtschattengewächse /The Nightshade Family, Museum Fridericianum, Kassel, 16.5.1993 - 8.8.1993
boek